John Vachon papers - Vachon, John, 1914-1975.
Correspondence, family papers, lecture notes, writings, financial papers, clippings, printed matter, and other material relating primarily to Vachon's career as a photographer with the U.S. Farm Security Administration, U.S. Office of War Information, Standard Oil Company of New Jersey, and Look magazine. Also documents his student days at Catholic University of America (1935-1936), life in Washington, D.C., (1935-1939), service in the U.S. Army at Camp Blanding, Fla. (1945), and work for the United Nations Relief and Rehabilitation Administration in Poland (1946). Subjects include the Great Depression, entertainers and authors such as Marilyn Monroe and Tennessee Williams, jazz, movies, politics, poverty, social life and mores in America, and World War II. Includes a transcript of a conversation in 1952 between Roy Emerson Stryker, director of the FSA project, and FSA photographers, including Dorothea Lange, Arthur Rothstein, and Vachon. Correspondents include Vachon's mother Ann O'Hara Vachon and his first wife Millicent Vachon.
Photographer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Lange, Dorothea; Monroe, Marilyn, -- 1926-1962.; Rothstein, Arthur, -- 1915-1985.; Stryker, Roy Emerson, -- 1893-1975.; Vachon, Ann O'Hara -- Correspondence; Vachon, Millicent -- Correspondence; Williams, Tennessee, -- 1911-1983.; United States. -- Army; United States. -- Farm Security Administration; United States. -- Office of War Information; Catholic University of America -- Students; Standard Oil Company of New Jersey; United Nations Relief and Rehabilitation Administration; Look; American periodicals -- New York (State) -- New York; Authors; Depressions -- 1929 -- United States; Entertainers; Jazz; Motion pictures; Photography -- Poland; Photography -- United States; Poverty -- United States; World War, 1939-1945.; Camp Blanding (Fla.); United States -- Economic conditions -- 20th century; United States -- Politics and government -- 20th century; United States -- Social conditions -- 20th century; United States -- Social life and customs -- 20th century; Washington (D.C.) -- Social life and customs; Photographers